Shell structures in civil and mechanical engineering theory and closed-form analytical solutions - Zingoni, Alphose (Thomas Telford, 1997)
This authoritative text concentrates on the derivation of simple but reasonably accurate mathematical solutions, and the actual presentation of closed-form results for quantities that are of interest to the designer of shell structures.